2007
DOI: 10.1111/j.1600-0781.2007.00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet A1 phototherapy for treatment of acrosclerosis in systemic sclerosis: controlled study with half‐side comparison analysis

Abstract: These results suggest that UVA1 phototherapy does not improve cutaneous thickness in acrosclerosis even if few functional improvements, and some ulcerations healings can be occasionally observed. However, a larger scale trial is necessary to confirm this inefficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 21 publications
0
21
1
Order By: Relevance
“…In contrast to the aforementioned results, the data of Durand et al (45), which was based on a controlled investigation, suggest that UV-A1 therapy is ineffective in acrosclerosis (45). Otherwise one must consider a systemic UV-A1 effect that could explain the results of Durand et al (45).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…In contrast to the aforementioned results, the data of Durand et al (45), which was based on a controlled investigation, suggest that UV-A1 therapy is ineffective in acrosclerosis (45). Otherwise one must consider a systemic UV-A1 effect that could explain the results of Durand et al (45).…”
Section: Introductionmentioning
confidence: 86%
“…Hence, this study also demonstrated that UV-A1 treatment is effective in SSc patients, particularly for acrosclerosis (44). In contrast, Durand et al (45) reported a randomized observer-blinded half-side controlled trial on UV-A1 treatment of acrosclerosis. They used low-dose UV-A1 (40 J/cm 2 ) three times per week (14 weeks treatment period).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, patients evaluated the skin pigmentation on the VAS (–50 mm, extremely depigmented; 0 mm, unchanged; +50 mm, extremely hyperpigmented) and efficacy of therapy (–50 mm, extreme worsening; 0 mm, unchanged; +50 mm, extreme improvement) before and after 1, 2, 3 and 4 weeks of irradiation and in the follow-up weeks 5 and 6. In several previous publications, VAS have been evaluated for their efficacy in determining different levels of cosmetic outcome or degrees of clinical improvement in dermatology [13,14,15]. Photographs of both the irradiated plaque and of the control plaque were taken every week.…”
Section: Methodsmentioning
confidence: 99%
“…Marked softening was noted in all four patients and there was a significant increase in joint passive range of motion, skin temperature and cutaneous elasticity (all with p values < 0.05). By contrast, a randomized, investigator-blinded study conducted by Durand et al with half-side comparison analysis in nine patients who received low-dose UVA1 (40 J/cm 2 three times per week for 14 weeks) phototherapy to one hand, demonstrated similar improvement in both hands as measured by the MRSS [41]. Moreover, no changes were evident regarding the index of flexion and extension in these patients (although two patients did note improved function in the treated hand).…”
Section: Systemic Sclerosis (Scleroderma)mentioning
confidence: 90%